Dynamic evaluation method of lower limbs joint alignment (MADAAMI) for dancers during the plié - Kaanda Nabilla Souza Gontijo; Cláudia Tarragô Candotti; Grace dos Santos Feijó; Laís Paixão Ribeiro; Jefferson Fagundes Loss
Abstract In classical ballet, the joint misalignments during the plié can generate various injuries. To evaluate potential misalignments during the plié the aim of this study was to present a method for dynamic evaluation of lower limb alignment articulation (called MADAAMI). MADAAMI was validated by 12 experts, and for the evaluation of its reproducibility and for agreement with 3D kinematics, 20 dancers were assessed using a video recording of their plié. For statistical analysis we used the Kappa coefficient (k) (p < 0.05) and percentage agreement (C). We conclude that MADAAMI had satisfactory reproducibility and intra-rater agreement with 3D kinematics (k > 0.40 and C > 80%), and it is a suitable and valid method for use by the same examiner.